2015
DOI: 10.1002/aelm.201500196
|View full text |Cite
|
Sign up to set email alerts
|

Improper Inversion Symmetry Breaking and Piezoelectricity through Oxygen Octahedral Rotations in Layered Perovskite Family, LiRTiO4 (R = Rare Earths)

Abstract: A signifi cant amount of research in the piezoelectric and ferroelectric communities is presently being dedicated to fi nding new electronic materials for applications in sensors, actuators, and transducers. This fi eld of research has long been dominated by AB O 3 perovskite oxides in which the inversion centers in the crystal structures are removed by atomic displacements due to the second-order Jahn-Teller (SOJT) effect. [1][2][3] There are only a few SOJT-active cations such as Ti 4+ and Zr 4+ with empty n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 46 publications
(129 reference statements)
3
28
0
Order By: Relevance
“…As a general observation, we note that the NCS P 2 1 m space group that we predict for 13 out of 19 compositions from DFT is also one of the most commonly observed experimental ground states 16 17 (also see Fig. 4 ) for the n =1 RP compounds.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…As a general observation, we note that the NCS P 2 1 m space group that we predict for 13 out of 19 compositions from DFT is also one of the most commonly observed experimental ground states 16 17 (also see Fig. 4 ) for the n =1 RP compounds.…”
Section: Resultssupporting
confidence: 73%
“…1b ). In the literature, the family of cation-ordered Na R TiO 4 and Li R TiO 4 (found only recently), where R =La, Nd, Dy, Gd, Sm, Ho, Eu and Y, have been experimentally shown 16 17 to have the piezoelectric P 2 1 m space group [ ( η 1 , η 1 ; η 1 )]. The nominal electronic configuration of Ti 4+ in these compounds is d 0 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phonon dispersion curves were drawn for a standard primitive cell 64,65 along a q-space path based on crystallography 66 . Our systematic stable structure exploration was conducted in a previously reported way 37,[67][68][69][70] .…”
Section: Methodsmentioning
confidence: 99%
“…13 It was also reported that acentricity is induced by oxygen octahedral rotations in A-site ordered n = 1 RP titanates ARTiO 4 (A = H, Li, Na, K; R = rare earth). [14][15][16][17] Hybrid improper ferroelectricity is also possible for n = 2 Dion-Jacobson (DJ) phases, 18,19 which is another type of layered perovskites consisting of primitive stacking of adjacent perovskite blocks, in contrast to bodycentered stacking in RP phases. In spite of the difference in stacking fashions, ferroelectricity induced by oxygen octahedral rotations was also theoretically predicted for the n = 2 DJ phases ARB 2 O 7 (A = Rb, Cs, R = La, Nd, B = Nb, Ta), 18,19 and indeed, these oxides were proven to be polar by means of synchrotron x-ray diffraction, neutron diffraction, and optical second harmonic generation measurements.…”
Section: Introductionmentioning
confidence: 99%